Meta-Analysis on the Roles of Fathers in Parenting: Are They Unique?. Issue 7 (2nd October 2016) - Jeynes, William H.
ABSTRACT: A meta-analysis was undertaken, including 34 studies, to determine whether fathers play a unique role in parenting that is different from mothers' roles. Statistical analyses were done to determine the extent to which the effects of fathering children were distinct from that of mothering. In addition to examining this phenomena overall, the meta-analysis also specifically examined social measurements, psychological indicators, and academic achievement. The possible unique effects of fatherhood were also examined in relation to the age and gender of the child. The results indicate consistent statistically significant effects that emerged for the unique role that fathers have. This association between fathering and the outcome variables held across social measurements, psychological indicators, and academic achievement. This relationship also held for both boys and girls and across age groups. The effects of the unique role of fathering yielded effect sizes of about .14 to .23 of a standard deviation unit.